Case study: co-creating Special Educational Needs and Disabilities (SEND)-friendly science resources for families - Pooley, Helen; Millward, Miranda; Hall, Vicky; McCormack, Elin (Frontiers in Education, 2025)
This community case study presents the process a multi-partner project took to develop accessible and engaging science-related activities for children with SEND and their families. Designed for use in museums, community outreach events, or at home, these resources reinforce science learning beyond the classroom. The History of Science Museum, RAL Space and Iffley Academy—a specialist school for children and young people with complex special educational needs and disabilities (SEND)—co-created a suite of outreach activities to be used by educators, ambassadors, parents or guardians to engage pupils with SEND in science. The project followed a relational model of engagement with classroom consultations with the same 11 pupils over several months, guided by a community outreach officer. Students made direct, significant contributions to the design and content of the resources. Co-creation ensured the resources were accessible and fostered an inclusive whole-family learning experience. The project has influenced the museum's and RAL Space's approaches to inclusive resource development and evaluation, while significantly improving the students' science capital and social-emotional development.